A Chronicle of the Timber Industry in East Arnhem Land, Australia - Pearson, Cecil; Helms, K. (InTech, 2012)
The north eastern part of the Northern Territory (NT) is East Arnhem Land. This expanse of Australia is the homeland of the Indigenous Yolngu clans whose forbears occupied the land some 50,000 years ago. These people survived in a nomadic lifestyle of hunter gatherers on their traditional land (Altman, 2002; 2003). Historical records show that from the 17th Century Indigenous Yolngu traded with seafarers from China, the Celebes, Japan, the Netherlands and even sailors navigating the great southern land (Berndt & Berndt, 1999; Worsely, 1955). Over 300 years later within the first quarter of the 20th Century, the Methodist Church began to develop the coastal region of East Arnhem Land, and thus, began the congregation of Indigenous communities (Trudgen, 2000). Living in this inhospitable land obliged the non Indigenous settlers to use available material to establish structures and facilities vital to sustain a string of mission stations. A primary resource was cypress pine (callitris intratropica) which was resistant to termites, the indefatigable predators of other timbers, and this was the beginning of merchandising the timber industry in East Arnhem Land. Within this chapter a number of places of interest are mentioned. Seldom are all of them to be found in a standard atlas as many are in the category of an outstation. While some of these isolated centres may have populations of 100 or more people others may have less than a handful of houses that at any time can be vacant as the people move from one to another location for cultural festivals, funerals or ceremonies. One location, which is likely to be found on a standard map, is the town of Nhulunbuy that acquires the name from the sacred Mt Nhulun, and by that translates from the local mother tongue language from where I come (i.e., I come from Nhulun). The town site of Nhulunbuy, which skirts Mt Nhulun, has some 4000 people, mostly non Indigenous. A majority of these people work in jobs associated with the mining operations as the refinery (12 km from the town) is one of the biggest in the southern hemisphere with a capacity of 3.8 million tonnes of alumina per annum. Nhulunbuy is on the Gove Peninsula and the region is home to about 8000 Indigenous Yolngu who live mainly at Yirrkala (about 800 people) and on outstations and hamlets as all the land is classified as native titled. Those places which are nominated in the following pages are identified in Figure 1.